Analisis Konsep Momentum dan Tumbukan pada Permainan Lato-Lato - Aufa Maulida Fitrianingrum; Kamaruddin Kamaruddin (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2023)
Clackers are one of the most popular toys in Indonesian society today. There are many physics concepts in this toys that can make clackers as a source of learning physics. The purpose of this research is to examine the concepts of physics, especially the concepts of momentum and collisions in clackers’ games. The method used in this study is a qualitative method with an explanation in the form of descriptive analysis. Literature study and observational analysis were used in this study. This study provides an illustration that every ball's motion in the clackers’ game contains the concept of momentum at each point of its motion and collision when the two balls collide. The results of this study are expected to explain that clackers have the potential as a source of learning physics.